A New Criterion for Prediction of Phase Stability in Al‐Containing High Entropy Alloys. Issue 3 (3rd November 2020) - Li, Fangjie; Sha, Yeyu; Zeng, Xin; Zhang, Shidong; Shi, Tao; Shen, Bingyu; Shen, Qin; Liu, Min
Abstract : The reliable phase formation rule is demanded for high entropy alloys' (HEAs) design and property regulation. Previous studies reveal the significant roles of thermodynamic and geometrical parameters in predicting phase structures of HEAs, whereas an accurate criterion is still not available. Herein, taking the most extensively studied Al‐containing HEAs as research object, two alloying parameters, i.e., d‐orbital energy level (Md) and bond order (Bo), combining with valence electron concentration (VEC) and atomic size difference ( δ ), are introduced to explore the phase stability of Al‐containing HEAs. The results indicate that single FCC solid solution tends to form in the range of δ below 4.5%, ordered phases (such as B2 and intermetallics) are more likely to be produced when the Md value of the alloy is beyond 1.06, and the FCC + BCC dual‐phase structures are mainly concentrated in the region of δ  > 4.5% and Md < 1.06. The Md– δ criterion provides a reliable criterion of phase stability and a good guidance in alloy design for Al‐containing HEAs. Abstract : Herein, a reliable phase formation rule for Al‐containing high entropy alloys (HEAs) using d‐orbital energy level (Md) and atomic size difference ( δ ) is reported. The Md– δ criterion reveals that HEA with δ below 4.5% tends to form FCC solid solution and the ordered phases (B2 or intermetallic compounds are easier to be produced in the HEA with Md beyond 1.06.